Attracting Attentive Academics. Paper, Person or Place? - Isabel Guenther; Melanie Grosse; Stephan Klasen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We examine the determinants of the number of attendees and questions and comments in parallel sessions at a large economics conference. We use the annual meeting of the German economics association in 2012 in G ttingen as an empirical case study. We find that the place (close to the coffee and before lunch) of the presentation is most important for attendance, whereas the person and the paper presented has a minor effect on other academics attending the presentation. However, papers with long titles as well as those by junior researchers attract significantly fewer attendees. There are also interesting and sizable gender effects. Sessions by female presenters are frequented more, but mainly because more women attend sessions in general, and sessions with female presenters in particular. Female researchers are also interested in different topics than male researchers. When it comes to asking questions, location becomes less important, but smaller rooms lead to more questions asked. Younger researchers attract more questions. Women ask fewer questions, but a large share of women increases the likelihood of a woman to ask a question. Our findings suggest that scheduling sessions should be taken more seriously to ensure better participation at conferences, and to take into account differences in preferences between men and female researchers.
Keywords: A11; B54; Z00; 330